Perancangan Interior Arsitektur Steak Hut Restaurant di Surabaya - Josephine Chintami Tjondrowibowo; Tri Noviyanto Utomo; Maria Yohana Susan (KREASI, 2015)
Nowadays, business are growing rapidly in many sectors especially in the property area, where interior and architecture is a part of it. The lifestyle differences has made people more concern about the importance of design in human being. This circumstance opens a great opportunities for designer to make a lot of new design and develop more interior style which can be accepted by other yet represent their own characteristic. In fact, Intericos Interior Consultant catch this opportunities to give new concept for design and gives solution to those who need it. Our company gives the best to be better than the other by maintaining the quality of work such as cafetaria, restaurant and bar, retail, etc. This will help people to find their own need.